The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1373/49.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Two Immunoassays for Human Glandular Kallikrein 2

Abstract: Background: Measurement of human kallikrein 2 (hK2) has improved early detection and staging of prostate cancer. However, reported concentrations of hK2 among currently used assays have not been standardized in any way. We compared two hK2 assays and five different recombinant hK2 variants (rhK2) and suggest a common calibrator as an important step and putative reference substance in hK2 assay standardization. Methods: We measured 146 sera by two hK2 assays, using assay-specific calibrators to assess the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Multicenter studies have shown that different total hK2 assays used to measure the exact same patient sample give significantly different results, leading to low correlation coefficients (57,58 ). Even small differences in the molecular structure (nicking, prosequences, or changes in amino acid composition) can affect the way hK2 is recognized by the capture or tracer antibodies (58 ). Therefore, the reaction patterns of different hK2 antibodies should be well characterized and care should be taken when comparing results obtained with different hK2 assays.…”
Section: Discussionmentioning
confidence: 99%
“…Multicenter studies have shown that different total hK2 assays used to measure the exact same patient sample give significantly different results, leading to low correlation coefficients (57,58 ). Even small differences in the molecular structure (nicking, prosequences, or changes in amino acid composition) can affect the way hK2 is recognized by the capture or tracer antibodies (58 ). Therefore, the reaction patterns of different hK2 antibodies should be well characterized and care should be taken when comparing results obtained with different hK2 assays.…”
Section: Discussionmentioning
confidence: 99%
“…Although standards are available for most clinically important analytes, reference methods for immunoassays are available only for haptens (1 ). The study of Haese et al (2 ) in this issue aims at standardization of assays for human kallikrein 2 (hK2); it highlights many of the problems associated with standardization of sensitive immunoassays and with the use of recombinant proteins as standards.…”
mentioning
confidence: 99%
“…On the tissue level, PSA expression decreases with increasing tumor grade (and aggressiveness), whereas hK2 expression is constant or less affected (3 ). Several studies indicate that this is reflected in an increased hK2/PSA ratio in serum, but this has not been observed in all studies (2 ). The somewhat conflicting results may be attributable to differences between the methods used or to insufficient analytical sensitivity of the assays.…”
mentioning
confidence: 99%
See 2 more Smart Citations